2018
DOI: 10.1038/s41598-018-31737-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frequency and strain-rate domain mechanical characterization

Abstract: Indentation is becoming increasingly popular to test soft tissues and (bio)materials. Each material exhibits an unknown intrinsic “mechanical behaviour”. However, limited consensus on its “mechanical properties” (i.e. quantitative descriptors of mechanical behaviour) is generally present in the literature due to a number of factors, which include sample preparation, testing method and analysis model chosen. Viscoelastic characterisation – critical in applications subjected to dynamic loading conditions – can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…A linear viscoelastic model was adopted to model biological tissues under cyclic loading, characterised by the storage and loss moduli. Further, methods to convert data from the frequency domain to time-domain are reported in literature [62]; further, the maximum strain rate in this study ranges approximately between 7-14 /s. Based on this approach, the frequency dependent values presented in this paper could be used to fit viscoelastic constitutive models such as through Prony series representations following adaptation of the storage and loss moduli obtained to represent the mechanical behaviour of brain tissue.…”
Section: Discussionmentioning
confidence: 88%
“…A linear viscoelastic model was adopted to model biological tissues under cyclic loading, characterised by the storage and loss moduli. Further, methods to convert data from the frequency domain to time-domain are reported in literature [62]; further, the maximum strain rate in this study ranges approximately between 7-14 /s. Based on this approach, the frequency dependent values presented in this paper could be used to fit viscoelastic constitutive models such as through Prony series representations following adaptation of the storage and loss moduli obtained to represent the mechanical behaviour of brain tissue.…”
Section: Discussionmentioning
confidence: 88%
“…Strain hardening from preloading can be avoided with strain-rate measurements which negate the use of a trigger force before the measurements. Bartolini et al [54] studied the viscoelastic response of nano-indented poly(dimethylsiloxane) strips and found that the apparent elastic moduli of previously strained samples were lower than non pre-strained samples.…”
Section: Description Of Viscoelastic Behavior Of Neat Neutralized Anmentioning
confidence: 99%
“…Rate-dependence of elastic response in polymer systems is well known and has been explained on the basis of different molecular motions at various time regimes [24]. Recent studies have reported dependence of elastic moduli on strain rate for virgin and prestrained pristine PDMS [25]. With its emergence as a leading material for flexible pressure sensors, the strain-rate dependence of mechanical properties of carbon-filled PDMS have been reported [14].…”
Section: Resultsmentioning
confidence: 99%